2023
DOI: 10.1186/s12891-023-06512-9
|View full text |Cite
|
Sign up to set email alerts
|

Post-surgery interventions for hip fracture: a systematic review of randomized controlled trials

Abstract: Background Interventions provided after hip fracture surgery have been shown to reduce mortality and improve functional outcomes. While some systematic studies have evaluated the efficacy of post-surgery interventions, there lacks a systematically rigorous examination of all the post-surgery interventions which allows healthcare providers to easily identify post-operative interventions most pertinent to patient’s recovery. Objectives We aim to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 175 publications
0
5
0
Order By: Relevance
“…A systematic review of RCTs evaluated post-surgery interventions for patients with hip fractures, including nutritional supplementation, among various other strategies such as rehabilitation, osteoporosis management, and fall prevention. This review highlighted the diversity of interventions tested and underscored the need for well-rounded postoperative care to improve outcomes in fragile hip fracture patients [ 103 ]. The included RCTs considered just calcium and vitamin D supplementation, while interventions to increase nutritional calcium intake by means of dairy products or other calcium sources were not mentioned [ 103 ].…”
Section: Calcium Intake and Hip Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of RCTs evaluated post-surgery interventions for patients with hip fractures, including nutritional supplementation, among various other strategies such as rehabilitation, osteoporosis management, and fall prevention. This review highlighted the diversity of interventions tested and underscored the need for well-rounded postoperative care to improve outcomes in fragile hip fracture patients [ 103 ]. The included RCTs considered just calcium and vitamin D supplementation, while interventions to increase nutritional calcium intake by means of dairy products or other calcium sources were not mentioned [ 103 ].…”
Section: Calcium Intake and Hip Fracturesmentioning
confidence: 99%
“…This review highlighted the diversity of interventions tested and underscored the need for well-rounded postoperative care to improve outcomes in fragile hip fracture patients [ 103 ]. The included RCTs considered just calcium and vitamin D supplementation, while interventions to increase nutritional calcium intake by means of dairy products or other calcium sources were not mentioned [ 103 ]. Calcium supplements (i.e., calcium carbonate or citrate) along with vitamin D compounds are often easily prescribed, but they are often not tolerated and not taken in the long term.…”
Section: Calcium Intake and Hip Fracturesmentioning
confidence: 99%
“…Previous research found that combining postsurgical interventions for patients with fragility hip fractures across inpatient and outpatient settings may be able to improve physical function recovery and discovered that 63% of the studies were related to rehabilitation or medication or nutrition supplementation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hip fracture is an acute surgical condition, and ~98% of patients warrant an operation requiring anesthesia 1 . As the geriatric group is often associated with frailty and multiple comorbidities, patients undergoing hip fracture surgery are at a significantly higher risk of perioperative mortality and morbidity, including postoperative delirium, respiratory complications, myocardial ischemia, and cerebrovascular accidents.…”
mentioning
confidence: 99%